2019
DOI: 10.1111/bjh.15790
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab in paroxysmal nocturnal haemoglobinuria and atypical haemolytic uraemic syndrome: 10‐year pharmacovigilance analysis

Abstract: Summary Eculizumab is the first and only medication approved for paroxysmal nocturnal haemoglobinuria (PNH) and atypical haemolytic uraemic syndrome (aHUS) treatment. However, eculizumab safety based on long‐term pharmacovigilance is unknown. This analysis summarises safety data collected from spontaneous and solicited sources from 16 March 2007 through 1 October 2016. Cumulative exposure to eculizumab was 28 518 patient‐years (PY) (PNH, 21 016 PY; aHUS, 7502 PY). Seventy‐six cases of meningococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
114
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(136 citation statements)
references
References 67 publications
15
114
2
2
Order By: Relevance
“…The long-term tolerability of eculizumab was consistent with its known adverse event profile from established indications [21][22][23][24][25], and no new safety signals were observed since the interim analysis of the open-label extension study [14].…”
Section: Discussionsupporting
confidence: 59%
“…The long-term tolerability of eculizumab was consistent with its known adverse event profile from established indications [21][22][23][24][25], and no new safety signals were observed since the interim analysis of the open-label extension study [14].…”
Section: Discussionsupporting
confidence: 59%
“…5,22 A long-term study of eculizumab for the treatment of PNH showed an overall rate of 0.25 meningococcal infections per 100 patient-years, with almost all patients having previously received meningococcal vaccination. 23 In this study, patients were required to be vaccinated against meningococcal infection within 3 years before, or at the time of, initiating study treatment. No cases of meningococcal disease were reported by the time of data cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…1). Eculizumab is approved by the FDA for the treatment of PNH, atypical haemolytic uraemic syndrome and, most recently, for refractory myasthenia gravis and NMOSD [164][165][166][167][168][169][170][171][172] .…”
Section: Targeting C5mentioning
confidence: 99%